Interpretation Qualification Proof toward Humiliation Performer or Libel in Social Media - Fermadi, Bayu; Sina, La; Syarifudin, La (Jurnal Mulawarman Law Review, 2018)
Information openess is needed by society, the improvement of information technology sector, electronic media and globalization happens almost in all life sectors. Technology improvement which is marked with internet can be operated by using electronic media such as computer or handphone. Through internet, information exchange can be done fast, accurate and with cheap cost. Therefore internet can be media to ease someone to do type of criminal act which based on informaton technology (cybercrime) such as, criminal ac like libel, pornography, gamling, account breaking, and etcetera. Related with libel via electronic media, as it is organized in Law Number 11 Year 2011 about Electronic Information and Transactions. Then this issue which is done and is also not missed from electronic media itself. The proof is issue which hold important role in investigation process in law. The provision about the criminal act method can be done toward person who is accused doing certain criminal act. This provision is organized in formal criminal law. Verification process becomes important because it will decides defendant fate. If proof result with proof of evidence which is determined with law does not enough proof the guilt which is accused to defendant, then defendant is freed from punishment. It is vice versa, if the defendant guilt can be proved with enough proof of evidence, then the defendant can be avowed guilty and will be punished according to valid law.